Cover Image. Issue 3 (16th October 2019) - Sun, Xiaoxiao; Wang, Ping; Sheng, Bowen; Wang, Tao; Chen, Zhaoying; Gao, Kang; Li, Mo; Zhang, Jian; Ge, Weikun; Arakawa, Yasuhiko; Shen, Bo; Holmes, Mark; et al.
Abstract : The cover image is based on the Original Article Single photon emission from a further confi ned InGaN/GaN quantum disc via reverse‐reaction growth by Xinqiang Wang et al., https://doi.org/10.1002/que2.20 .